Atovaquone/proguanil‐induced autoimmune‐like hepatitis. Issue 4 (8th May 2017) - Terziroli Beretta‐Piccoli, Benedetta; Mieli‐Vergani, Giorgina; Bertoli, Raffaela; Mazzucchelli, Luca; Nofziger, Charity; Paulmichl, Markus; Vergani, Diego
Abstract : We report a novel association between the commonly used antimalarial medication atovaquone/proguanil and drug‐induced autoimmune‐like hepatitis. The patient developed severe liver disease fulfilling biochemical, immunologic, and histologic criteria for the diagnosis of autoimmune hepatitis after the inadvertent rechallenge with the offending drug, which had caused self‐limited hepatitic symptoms a year previously. Over a period of 18 months, the patient underwent two follow‐up liver biopsies showing progressive resolution of the liver inflammation and achieved complete biochemical and immunologic remission on steroids. This remission persisted for 20 months following treatment withdrawal. Conclusion : This well documented case raises awareness of the potential hepatotoxicity of atovaquone/proguanil. ( Hepatology Communications 2017;1:293–298)